Market Structure and Technical Efficiency of Banks in the MENA Region - José Manuel Maside-Sanfiz; Ana Iglesias-Casal; Qusay Ayman Sulaiman Mazahreh; Carmen López-Andión (SAGE Open)
The banking sector is the main source of finance for firms in the Middle East and North Africa (MENA) region and has certain peculiarities, for example, the significant presence of Islamic banking and low levels of competition. This study examines the influence of market structure (concentration and competition) on efficiency in a sample of 239 banks operating in the MENA region over a period from 2011 to 2020. Banking efficiency scores have been obtained with the Data Envelopment Analysis (DEA), the level of concentration has been measured by the Herfindahl-Harshman index and competition has been proxied by the bank-level Lerner index. We have assessed the relationship between competition and concentration on efficiency using Simar and Wilson’s two-stage approach. The robustness has been tested using the Generalized Method of Moments (GMM) system to mitigate potential endogeneity. The results indicate that concentration influences efficiency positively and market power negatively; in terms of the interaction between both variables, bank efficiency increases, in line with the bank specificity hypothesis (BSH). Although previous papers have used various indicators of concentration and competition, to our knowledge, this study is the first to examine their combined effects on bank efficiency in the MENA region. In addition, bank-specific characteristics (size, profitability, and capitalization) and bank type (Islamic, domestic) positively affect efficiency, as do indicators of financial inclusion, institutional framework, and financial development. These aspects allow us to extract relevant results that offer a number of practical implications for managers and policy makers to improve bank efficiency. JEL Classification: G2, G21, F37.